2017
DOI: 10.1002/jcb.25868
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Palmitate-Induced Inflammation in Skeletal Muscle Cells by Attenuating Oxidative Stress and JNK/NF-κB Pathway in a SIRT1-Independent Mechanism

Abstract: Resveratrol has been shown to exert anti-inflammatory and anti-oxidant effects in a variety of cell types, however, its role in prevention of inflammatory responses mediated by palmitate in skeletal muscle cells remains unexplored. In the present study, we investigated the effects of resveratrol on palmitate-induced inflammation and elucidated the underlying mechanisms in skeletal muscle cells. The results showed that palmitate significantly enhanced TNF-α and IL-6 mRNA expression and protein secretion from C2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…As expected, the mitochondrial membrane potential and total ATP level were substantially reduced along with the reduction in the mitochondrial electron transport chain complex proteins in CCCP‐treated myotube cells (Figure A,B). Mitochondrial dysfunction is known to increase intracellular ROS generation . As shown in Figure C, the intracellular ROS levels were drastically elevated and the reduced by pretreatment with the antioxidant N‐acetylcysteine (NAC) in C2C12 myotubes.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…As expected, the mitochondrial membrane potential and total ATP level were substantially reduced along with the reduction in the mitochondrial electron transport chain complex proteins in CCCP‐treated myotube cells (Figure A,B). Mitochondrial dysfunction is known to increase intracellular ROS generation . As shown in Figure C, the intracellular ROS levels were drastically elevated and the reduced by pretreatment with the antioxidant N‐acetylcysteine (NAC) in C2C12 myotubes.…”
Section: Resultsmentioning
confidence: 98%
“…Mitochondrial dysfunction is known to increase intracellular ROS generation. 22,23 As shown in Figure 3C, the intracellular ROS levels were drastically elevated and the reduced by pretreatment with the antioxidant N-acetylcysteine (NAC) in C2C12 myotubes. Next, we measured the proteins related to the mitochondrial dynamics and found that the levels of Mfn1, Mfn2 and the long form of OPA1 gradually decreased, while the expression of Fis1 increased upon treatment with CCCP and these effects were rescued by pretreatment with the antioxidant N-acetylcysteine (NAC) in C2C12 myotubes ( Figure 3D,E).…”
Section: Cccp-induced Mitochondrial Dysfunction Accompanies Muscle mentioning
confidence: 96%
“…However, none of them are able to point out a compound as responsible for a specific action. Previous studies using other food sources or isolated bioactive compounds evidenced that phenolic compounds (for example, quercetin, chlorogenic acid, caffeic acid, and rosmarinic acid), dietary fiber, fatty acid (for example, ALA), and others play a role in repairing health conditions triggered by unbalanced diets (Gonzalez‐Manan et al., ; Pal & Ghosh, ; Sadeghi, Seyyed Ebrahimi, Golestani, & Meshkani, ). Nevertheless, regarding chia seed, it is hard to link the effect on metabolism to one specific compound.…”
Section: Resultsmentioning
confidence: 99%
“…NF-κB was key to the inflammatory action due to its regulatory role on the expression of a variety of cytokines (such as TNF-α and IL-6) that regulate the inflammatory response (25,45). As a regulator of death and survival proteins, NF-κB serves an important role in neuron survival in the CNS.…”
Section: Discussionmentioning
confidence: 99%